2017
DOI: 10.7554/elife.20975
|View full text |Cite
|
Sign up to set email alerts
|

Transient inhibition and long-term facilitation of locomotion by phasic optogenetic activation of serotonin neurons

Abstract: Serotonin (5-HT) is associated with mood and motivation but the function of endogenous 5-HT remains controversial. Here, we studied the impact of phasic optogenetic activation of 5-HT neurons in mice over time scales from seconds to weeks. We found that activating dorsal raphe nucleus (DRN) 5-HT neurons induced a strong suppression of spontaneous locomotor behavior in the open field with rapid kinetics (onset ≤1 s). Inhibition of locomotion was independent of measures of anxiety or motor impairment and could b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
91
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(104 citation statements)
references
References 90 publications
(145 reference statements)
11
91
0
Order By: Relevance
“…Another study showed that the activation of axons in VTA from DR caused sustained reinforcement effects and the release of dopamine in the NAc, suggesting that although serotonin neurons mediate signaling for reinforcement, serotonin may not cause sustained effects directly at the projection sites for reinforcing behavior. Other studies have not observed the reinforcement effects of serotonin neurons following stimulation in the soma . Therefore, sustained effects of serotonin are evident in specific contexts, such as reversal learning and social conditioning.…”
Section: Sustained Dopamine and Serotonin Effects On Behaviormentioning
confidence: 91%
See 2 more Smart Citations
“…Another study showed that the activation of axons in VTA from DR caused sustained reinforcement effects and the release of dopamine in the NAc, suggesting that although serotonin neurons mediate signaling for reinforcement, serotonin may not cause sustained effects directly at the projection sites for reinforcing behavior. Other studies have not observed the reinforcement effects of serotonin neurons following stimulation in the soma . Therefore, sustained effects of serotonin are evident in specific contexts, such as reversal learning and social conditioning.…”
Section: Sustained Dopamine and Serotonin Effects On Behaviormentioning
confidence: 91%
“…During engaging in the task, serotonin stimulation did not affect motor behavior for approaching to cues . However, in another behavioral context of free‐moving in the open field, stimulation of serotonin neurons in the DR inhibited spontaneous locomotion acutely within 1 s and the termination of stimulation recovered locomotion within 4 s, suggesting that serotonin inhibited locomotion behavior transiently . Interestingly, suppression of locomotion was not observed when mice engaged in tasks such as rotarod or reward‐approaching tasks, suggesting that serotonin indirectly modulates factors that drive behaviors .…”
Section: Effects Of Transient Dopamine and Serotonin On Behaviormentioning
confidence: 93%
See 1 more Smart Citation
“…In light of these and other related experiments, Jacobs and Fornal suggested that the serotonergic system is especially involved in facilitating the motor output involved in central pattern generators, and in relation to the behavioral state (Lydic & Baghdoyan, ). In accordance with this hypothesis, the optogenetic stimulation of serotonergic neurons in the DRN modulates certain motor activity types (Correia et al, ).…”
Section: Discussionmentioning
confidence: 85%
“…Despite theoret- 37 ical suggestions for an association with aversive learning [19,53,13,6,15], direct 38 experimental tests into serotonin's role in RL tasks have led to a complex pattern of 39 results [12,52,42,45,22,11]. For instance, recent optogenetic studies reporting that 40 stimulating 5-HT neurons could lead to positive reinforcement [42] do not appear to 41 be consistent with other optogenetic findings, which instead suggest an involvement 42 with patience [22,45] and even locomotion [11]. 43 Here, we study a different aspect of the involvement of 5-HT in RL.…”
mentioning
confidence: 99%